Return to work and lost earnings after acute respiratory distress syndrome: a 5-year prospective, longitudinal study of long-term survivors - Kamdar, Biren B (Thorax, 2017)
BACKGROUND: Delayed return to work is common after acute respiratory distress syndrome (ARDS), but has undergone little detailed evaluation. We examined factors associated with the timing of return to work after ARDS, along with lost earnings and shifts in healthcare coverage. METHODS: Five-year, multisite prospective, longitudinal cohort study of 138 2-year ARDS survivors hospitalised between 2004 and 2007. Employment and healthcare coverage were collected via structured interview. Predictors of time to return to work were evaluated using Fine and Grey regression analysis. Lost earnings were estimated using Bureau of Labor Statistics data. RESULTS: Sixty-seven (49%) of the 138 2-year survivors were employed prior to ARDS. Among 64 5-year survivors, 20 (31%) never returned to work across 5-year follow-up. Predictors of delayed return to work (HR (95% CI)) included baseline Charlson Comorbidity Index (0.77 (0.59 to 0.99) per point; p=0.04), mechanical ventilation duration (0.67 (0.55 to 0.82) per day up to 5 days; p<0.001) and discharge to a healthcare facility (0.49 (0.26 to 0.93); p=0.03). Forty-nine of 64 (77%) 5-year survivors incurred lost earnings, with average (SD) losses ranging from US$38 354 (21,533) to US$43 510 (25,753) per person per year. Jobless, non-retired survivors experienced a 33% decrease in private health insurance and concomitant 37% rise in government-funded coverage. CONCLUSIONS: A cross 5-year follow-up, nearly one-third of previously employed ARDS survivors never returned to work. Delayed return to work was associated with patient-related and intensive care unit/hospital-related factors, substantial lost earnings and a marked rise in government-funded healthcare coverage. These important consequences emphasise the need to design and evaluate vocation-based interventions to assist ARDS survivors return to work.